Estudo da cinética e influência dos métodos de secagem sobre as propriedades físico-químicas de soro de leite - Paula, Ramon Ramos de (2015)
Whey is a product of cheese manufacturing, either by acidification or by enzymatic process. Ideally, the milk casein is aggregate to form a gel, later cut when the separation thereof occurs. It is used of various forms within the food industry, has a high levels of lactose, minerals and proteins in the composition and dehydration is one of the major processing procedures and processing whey. Hence, the objective of this study was to evaluate the influence of the drying methods: freeze drying, foam-mat drying (in temperatures of 40, 50, 60, 70 and 80ºC) and spray-dryer (in temperatures of 55, 60, 65, 70 and 75°C) on the moisture characteristics, protein, color and solubility of the whey as well as studying your drying process. The whey was obtained and dehydrated after concentration by reverse osmosis, testing 11 treatments and 3 replications, using a completely randomized design. The results showed that the mathematical model best fit was the Page's model, with a coefficient of determination adjusted above 0.98 and standard error of the regression at all temperatures below 0.04 for the foam-mat drying. In the lyophilization method, the respective values were 0.9975 and 0.01612. From this a generalized mathematical model could be achieved, with a coefficient of determination same to 0.9888. In the case of the foam-mat drying was observed that as one increases the temperature of the drying air, the drying time decreases and values of the effective diffusion coefficient increases. However, the reduction in drying time between the intervals of temperature decreases with the increase of the same. The activation energy for diffusion of whey at drying process was 26.650 kJ/mol and in all physico-chemical and technological assessments, analysis of variance showed a significant F value (p <0.05), indicating that there are at least a contrast between the treatments that is significant.